2013
DOI: 10.1002/fam.2176
|View full text |Cite
|
Sign up to set email alerts
|

Fire characteristics of steel members coated with nano‐enhanced polymers

Abstract: Polymeric coatings applied to masonry infill walls have been demonstrated to provide protection against blast. Steel frames may be embedded in these walls to improve the structural characteristics of the building. During the process of retrofitting the walls with blast protection polymeric coatings, the steel frame may be fully or partially coated with these materials to provide adequate anchorage of the retrofit system to the frame and to avoid global failure of walls subjected to blast loading. The developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Constant values of density, conductivity, and specific heat have been used in the absence of better information as in previous numerical works. 15,35–43,54 This is supported by the studies based on simulation results by Stanislav et al, 55 where it was concluded that the effect of these parameters is of little importance on the burning behavior of polymers versus other parameters affecting combustion. However, accounting for density, heat capacity, and thermal conductivity dependence with the temperature and decomposition may improve the simulation in the future.…”
Section: Materials Experimental Methods and Input Parametersmentioning
confidence: 74%
See 2 more Smart Citations
“…Constant values of density, conductivity, and specific heat have been used in the absence of better information as in previous numerical works. 15,35–43,54 This is supported by the studies based on simulation results by Stanislav et al, 55 where it was concluded that the effect of these parameters is of little importance on the burning behavior of polymers versus other parameters affecting combustion. However, accounting for density, heat capacity, and thermal conductivity dependence with the temperature and decomposition may improve the simulation in the future.…”
Section: Materials Experimental Methods and Input Parametersmentioning
confidence: 74%
“…The analytical definition of the viscosity–temperature curves used is given in Table 6 and plotted in Figure 9. For estimating the viscosity value for those ranges where the curve is not available, the procedure presented in Butler et al 42 is used. While the viscosity in the jacket is a function of temperature, the viscosity of the core is considered as constant and set to a very high value.…”
Section: Materials Experimental Methods and Input Parametersmentioning
confidence: 99%
See 1 more Smart Citation